Beguru: An Ethno-education of Sasak, Indonesia (Exploring the Principles of Learning Processes & Evaluation) - Lalu Sumardi; M Ismail; Rispawati rispawati; Dwi Wahyudiati (Journal of Innovation in Educational and Cultural Research, 2022)
Each ethnic group has its own local wisdom, which serves as a compass for their life, including in the education sector. Beguru is local wisdom of the Sasak community, Indonesia in education that is rich with principles. This study aims to explore principles of beguru in relation to the learning process and evaluation. The study applied an ethnography-type naturalistic approach. Data was collected by means of ethnographic interviews and observations. Data analysis employed interactive models proposed by Miles, Huberman, Saldana, comprising three stages: data condensation, data display, and conclusion. Based on the method, the study identified 4 principles related to the learning process and 2 principles related to learning evaluation. The four principles of beguru related to the learning process include 1) ethics principle, 2) mastery learning principle, 3) individual learning principle, and 4) learning acceleration principle. While the two principles of beguru related to learning evaluation, include: 1) holistic principle, and 2) concurrent principle. The principles are strongly adhered to during beguru resulting in effective, efficient learning processes and optimum realization of expected competencies. The above principles are very appropriate to apply in contemporary education for improving the quality of learning processes and outcomes.